Hubungan Cara Persalinan dengan Apgar Score pada Kasus Ketuban Pecah Dini di RSUD Dr. Moewardi - Stephanie Indrawati Sugiarto; Affi Angelia; Novi Primadewi (Nexus Kedokteran Klinik, 2013)
Background: Premature rupture of membrane (PROM) occurs when amniotic membranes rupture without the signs of delivery. PROM occurs in 6 8% pregnancies and about 80% PROM occurs at term gestational age (>37 weeks). PROM is always terminated for preventing complication whether in mother and baby. Previews studies assumed that delivery process can affect the Apgar score of the newborn. This study aimed to know the relationship between delivery process with Apgar score in premature rupture of membrane case. Methods: This analytic study was observational using cohort retrospective approach. 151 study subjects were selected by fixed exposure sampling and simple random sampling from all PROM cases on January 2011 December 2012 period at RSUD Dr. Moewardi and fulfill the intrinsic and extrinsic criteria. The data was collected from medical record. The data was analyzed using Chi square test and binary logistic regression test with Odd Ratio (OR) which shows the score of the relationship on SPSS 20 for windows. Result: This study showed that Sectio cesaria increases the risk of worse Apgar score than labor induction, although there is no significant relationship between delivery process with Apgar score in Chi square test (p = 0.198; OR = 1.861). So do the analysis multivariate with binary logistic regression test shows p = 0.404 and OR = 1.607. Conclusion: Sectio cesaria increases the risk of worse Apgar score than labor induction in PROM case at RSUD Dr. Moewardi. Keyword: premature rupture of membrane, delivery process, Apgar score.